Development of a diagnostic ELISA for the hepatitis B x-protein using monoclonal antibodies - Mashinini, Bongiwe (My University, 2010)
The hepatitis B virus remains a major public health problem even after decades of its discovery. Horizontal transmission during early childhood is the predominant mode of transmission in highly endemic regions such as sub-Saharan Africa. Infection exhibits a wide spectrum of clinical manifestations, from an asymptomatic stage to severe liver disease which may result in hepatocellular carcinoma (HCC). The HBV X protein (HBx) has been implicated in carcinogenesis, which often has a poor prognosis, consequently the use of highly specific monoclonal antibodies (mAbs) directed against HBx in an enzyme-linked immunosorbent assay (ELISA) could lead to early identification of HBV carriers at risk of developing liver cancer. A variety of mixed hybridoma cell cultures secreting anti-HBx antibodies were cloned and sub-cloned by “limiting dilution”. Clonal supernatants were assessed for anti-HBx antibody production by Indirect ELISA and Western/Immunoblotting. Monoclonal antibodies were then characterized according to their relative binding affinity (Indirect ELISA) and relative epitope specificity (Competitive ELISA). One of our monoclonal antibodies was found to bind to the same epitope on HBx as the commercial anti-HBx antibody and with the same high affinity. In the developed Sandwich ELISA, our monoclonal antibody proved effective as the „detecting‟ antibody when the commercial anti-HBx antibody was deployed as the „capture‟ antibody. This Sandwich ELISA will be further developed in our laboratory with the object of applying it to patient sera.
MSc (Med), Faculty of Health Sciences, University of the Witwatersrand
Keywords: Hepatitis B virus; enzyme-linked immunosorbent assay